ANALISIS FINANCIAL DISTRESS PT SARIMELATI KENCANA TBK DENGAN METODE SPRINGATE - Wahyuni, Anissa; Purwati, Purwati; Lupikawaty, Marieska (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research investigates the likelihood of financial distress experienced by PT Sarimelati Kencana Tbk throughout the 2019–2023 period by applying the Springate model. A descriptive quantitative method was utilized, utilizing secondary information obtained from the firm’s yearly financial reports. Findings indicate that the firm maintained a financially sound status solely in the year 2019. From 2020 to 2023, the scores were below the threshold, indicating that PT Sarimelati Kencana was experiencing financial distress. The method demonstrated an accuracy rate of 80% with no kesalahan tipe I errors and a weighted error rate of 20%. These findings indicate that the Springate method is sufficiently sensitive in identifying financial pressure in companies. It is advised that the company prioritize enhancing its cash flow management, optimizing operational processes, and reinforcing its digital initiatives to improve overall financial stability and achieve a sustainable recovery from financial challenges.